(untitled) (The Review of Diabetic Studies, 2025)
Laboratory services play a pivotal role in modern healthcare systems by supporting accurate diagnosis, guiding treatment decisions, and enabling effective coordination among multidisciplinary clinical teams. As patient care increasingly relies on integrated and collaborative models, the contribution of laboratory services has expanded beyond test execution to active participation in clinical decision-making processes. This review aims to synthesize current evidence on the impact of laboratory services on multidisciplinary clinical decision-making and integrated patient care. A comprehensive review of peer-reviewed literature published between 2016 and 2025 was conducted across major biomedical databases, focusing on studies that examined laboratory involvement in multidisciplinary teams, clinical workflows, and patient outcomes. The findings indicate that timely and accurate laboratory data significantly enhance diagnostic precision, reduce medical errors, improve communication among healthcare professionals, and support personalized treatment planning. Effective integration of laboratory services within multidisciplinary teams was also associated with improved care coordination, patient safety, and clinical efficiency across various healthcare settings. The review highlights the strategic importance of laboratory services as a core component of integrated care models and emphasizes the need for stronger collaboration, optimized communication pathways, and supportive health system policies to maximize their impact on patient-centered care.